Enhancing quality of service: A conceptual poka-yoke approach - Alghozali, Fachrul Iman; Jamaludin, Roslan; Bahaudin, Ahmad Yusni (UUM College of Business, 2016)
Vending machine is one of the most widely used machines by the consumer.Many improvements have been made to improve the capability of vending machines.However, there are quality issues on products dispensed by the machines.In this study, the product expiration date is the main focus. Unlike buying food from the convenience stores where the expiry date for each product is readable, consumer are able to see the product expiry date only after having paid and product dispensed by the vending machine.Hence, consumer has negative perceptions of the company producing the products and also the vending machine service providers.This study emphasizes on improving the vending machines using automatic date-based switch as a poka-yoke device to improve quality of service.Qualitative approach is conducted through interview with a service provider company operating and maintaining vending machines. The result of this study revealed that the current manual maintenance have a major flaw and by adopting the poka-yoke approach on vending machines can improve the quality of service of products dispensed by the machines. Hence, The purpose of this paper is to describe issues and the improvement to quality of service on vending machine services industry by adopting a poka-yoke approach.